A. macrocephala polysaccharide induces alterations to gut microbiome and serum metabolome in constipated mice. (May 2023) - Yang, Huining; Wu, Chuntao; Chen, Lei; Chang, Xiangbing; Luo, Guofu; Wu, Kun; Tian, Wei
Abstract: Atractylodes macrocephala polysaccharide (AC1) is extracted from the root of the Chinese herb Atractylodes Macrocephala and is used in the treatment of constipation due to its effects on strengthening cellular immunity and regulating intestinal function. In this study, Metagenomics and Metabolomic are used to analyze the effects of AC1 on the gut microbiota and host metabolites in mice models of constipation. The results show that the abundance of Lachnospiraceae_bacterium_A4, Bact-oides_vulgatus and Prevotella_sp_CAG:891 increased significantly, indicating that AC1-targeted strain modulation effectively alleviated the dysbiosis of the gut microbiota. Besides, the microbial alterations also influenced the metabolic pathways of the mice, including tryptophan metabolism, unsaturated fatty acid synthesis and bile acid metabolism. The physiological parameters of the mice treated with AC1 are improved, such as tryptophan in the colon, 5-hydroxytryptamine (5-HT) and short-chain fatty acids (SCFAs). In conclusion, AC1 as a probiotic can regulate intestinal flora to normal levels and achieve the effect of treating constipation. Highlights: Pharmacodynamic effects of Atractylodes macrocephala polysaccharide extract on mice with spleen-deficiency constipation. HPLC and Infrared Spectroscopy were used for the analysis of Atractylodes macrocephala polysaccharide. AC1 alters the structure of gut microbiota and metabolites in mice with spleen-deficiency constipation.